Factors Affecting Collaboration Portal Effectiveness of the Audit Board of Indonesia - Afrialdi Syahputra; Paulus Insap Santosa; Rudy Hartanto (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
The Audit Board of the Republic of Indonesia is known as Badan Pemeriksa Keuangan (BPK). In carrying out its duties and functions, it empowers and relies on information technology (IT) infrastructure that covers all aspects, including planning, procurement, service provision, information asset security, service continuity, and evaluation. BPK implements a collaboration portal to meet service needs and teamwork during the audit process, ad-hoc committees, and leader instructions to follow BPK’s strategic plan. BPK needs to assess the effect of the collaboration portal in supporting employee performance and improving IT services. As a result, this study aims to investigate the factors that influence the effectiveness of the BPK collaboration portal. This study used Delone and McLean model of information system success by looking at the relationship of system quality, information quality, service quality, facilitating conditions, and collaboration quality to user satisfaction and individual job performance. The research method used a quantitative approach with partial least squares-structural equation modeling (PLS-SEM). The sample data was collected from 60 respondents at BPK. The data obtained from the respondents were processed using the SmartPLS application. The study results show that information quality, facilitating conditions, and collaboration quality positively and significantly affect user satisfaction. There is a positive and significant influence of user satisfaction on individual job performance. In addition, system quality and service quality do not significantly influence user satisfaction with collaboration portal services.